2012
DOI: 10.1016/j.jacc.2012.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Outcomes of Heart Rate Reduction by Ivabradine in Patients With Congestive Heart Failure: Is There an Influence of Beta-Blocker Dose?

Abstract: The magnitude of heart rate reduction by beta-blocker plus ivabradine, rather than background beta-blocker dose, primarily determines subsequent effect on outcomes. (Effects of ivabradine on cardiovascular events in patients with moderate to severe chronic heart failure and left ventricular systolic dysfunction. A three-year randomised double-blind placebo-controlled international multicentre study; ISRCTN70429960)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
152
1
23

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(189 citation statements)
references
References 22 publications
10
152
1
23
Order By: Relevance
“…27 The magnitude of heart rate reduction caused by beta-blocker and ivabradine, rather than background beta-blocker dose, primarily determines subsequent effect on outcomes. 28 The beneficial effects of ivabradine in SHIFT population was confirmed in all subgroups including patients with diabetes, arterial hypertension, concomitant treatment with MRAs or beta-blocker treatment and chronic obstructive pulmonary disease. [29][30][31][32][33] Furthermore, the effect of heart rate reduction with ivabradine is maintained regardless of presence and number of co-morbidities.…”
Section: Effects On Rehospitalisation and Mortalitymentioning
confidence: 83%
“…27 The magnitude of heart rate reduction caused by beta-blocker and ivabradine, rather than background beta-blocker dose, primarily determines subsequent effect on outcomes. 28 The beneficial effects of ivabradine in SHIFT population was confirmed in all subgroups including patients with diabetes, arterial hypertension, concomitant treatment with MRAs or beta-blocker treatment and chronic obstructive pulmonary disease. [29][30][31][32][33] Furthermore, the effect of heart rate reduction with ivabradine is maintained regardless of presence and number of co-morbidities.…”
Section: Effects On Rehospitalisation and Mortalitymentioning
confidence: 83%
“…This effect persisted after adjustment for baseline beta blocker dose 8. A meta‐analysis of the effects of beta blockers on outcome showed that achieved heart rate, not beta blocker dose, predicted outcome 16.…”
Section: Discussionmentioning
confidence: 96%
“…Heart rate is a simple and prognostic surrogate of sympathetic activity,8, 9 but its value depends on numerous factors besides sympathetic activation. Exercise heart rate and heart rate variability are other indirect markers that reflect the balance between sympathetic and parasympathetic activities,10 but they are not routinely measured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En los últimos tiempos a estas medidas (uso de inhibidores del Enzima conversor de angiotensina/bloqueadores del receptor de angiotensina, implantación de dispositivos cardioversoresdesfibriladores, anticoagulación para la fibrilación auricular y medidas educadoras en IC 5 y seguramente también el uso de agonistas de aldosterona 6 , se ha unido la ibavradina que ha mostrado aumentar la supervivencia y disminución de hospitalizaciones en IC 7 . La presente publicación de actualización sobre la IC, surge como consecuencia de la colaboración de las secciones gallegas de la Sociedad Española de Cardiología y de Medicina interna (SOGACAR y SOGAMI), que son las especialidades mayoritariamente encargadas de su manejo.…”
unclassified